PERBEDAAN STATUS GIZI BALITA ANTARA SEBELUM DAN SETELAH PENERAPAN CARE FOR CHILD DEVELOPMENT (CCD) - Eka Oktavianto (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2016)
Background: Nutritional problems of children less than five years is still one important child health problem in the world. This can occur as a result of poverty, health care is still bad, poor nutrition, and infection. Care for child development training (CCD) to cadres and the aplication, could be one of the efforts to overcome it Objective: The study was conducted to assess the diferences of nutritional status of the children before and after CCD training on cadreMethods: A pre-experimental design  one group with pretest and posttes was used in this study. Cadre and children 6-60 months in Puskesmas Mantrijeron Yogyakarta were included in this research. Cadres of were given CCD training for two days, and then they counsel to the caregiver. CCD module for cadres and facilitators, video, and counseling cards were used as instruments. Nutritional status of childrens measured a week before and three months after the training CCD. Bivariate data analysis using Marginal homogeneity test.Results: 13 cadres and 60 childrens were enrolled in this study. The results showed that 12 childrens had an increase in nutritional status. There was 1 child (1.7%) very thin nutritional status becomes non-existent. Likewise, originally there were 14 childrens (23.3%) underweight to five (8.3%) after given intervention. There were significant differences in the nutritional status between before and after the intervention (p 0.05).Conclusion: There were significant differences in the nutritional status between before and after the intervention (p 0.05). CCD training on cadre followed by counseling by the cadres to the mothers can improve the nutritional status of childrens. Keywords: CCD training, cadres, children, nutritional status.